Research on Gear Modification and Simulation of Hybrid Transmission - Dai Jianhua; Chen Weiwei; Jiang Jibin; Chen Xuewen; Zhang Hui (Jixie chuandong)
To deal with the phenomenon of partial load of the hybrid transmission gear pair in the actual working process and to solve the eccentric load problems of a hybrid light transmission gear pair, the gear analysis software Romax is used for 3D modeling of the meshing helical gears; one gear pair is simulated and analyzed under the commonly used operating conditions of the hybrid transmission set for operation, and the second-generation genetic algorithm is used for gear modification. The modification results show that the transmission error value, contact load and maximum contact stress of the gear pair are reduced under different working conditions, the offset load of the gear face is improved, and the meshing performance and life of the gear pair are improved, which provides some reference for the modification of the hybrid transmission gear.